Efeito da suplementação oral de glutamina sobre o estresse oxidativo em indivíduos de meia idade e idosos - Galera, Siulmara Cristina (2008)
Significant alterations in the organism occur in the human aging process, including the increase of oxidative stress which has been held responsible for unleashing many degenerative diseases. The adoption of a strategy able to interfere in the oxidative process would be essential to ease or retard the appearance of disorders prevailing in advanced age. The usage of substances in nutraceutic dosages as antioxidants precursors has been much studied. Safety and effects of the oral L-glutamine supplementation, in nutraceutic dosages,on oxidative stress and glucose metabolism were analyzed in middle-aged and elderly individuals. Thus, a randomized, controlled, cross-over, double-blind clinic trial was performed. Through the SENIEUR test protocol criteria with modifications, 32 people living in a nursing home were selected, divided in 2 groups and submitted to oral L-glutamine and calcium caseinate supplementation at the dosage of 0.5/kg/day for a 14-day period intercalated by a 5-day washout period. Tests were performed in order to evaluate hematological, hepatic, renal alterations and the estimated Glomerular Filtration Rate (eGFR) was calculated, the antioxidant capacity was evaluated through the total glutathione dosage,calculation of GSH/GSSG ratio of the redox (oxidation-reduction) potential through the Nerst equation and the lipid peroxidation was evaluated through dosage of TBARS (thiobarbituric acid reacting substances), before (T0) and after (T1) supplementation. From 32 participants that started the study, one was excluded due to anti-inflammatory usage and the other withdrew by own will. 16 (53.3%) out of 30 were men, average age 69 } 8.8 years, average weight 61.8 } 14.2 kg, serum albumine 4.0 } 0.3 g/dl. There was no clinical adverse effect during the L-glutamine usage, nor significant clinical alteration of laboratory parameters except for an increase in urea levels either at the caseinate group (T0= 34.100 } 9.117; T1 = 44.200 } 8.833; p<0.0001) as at the glutamine group (T0 = 34.100 } 9.117; T1 = 44.200 } 8.833; p<0.0001) and a statistically significant creatinine increase at the glutamine group (T0 = 0.917 } 0.123; T1 = 1.050 } 0.138; p<0.0001) and at the GFRe: 13.3% in Lglutamine supplementation and 2.9% in calcium caseinate supplementation, but without clinical significance. Blood levels of the Total Glutathione did not show alteration with Lglutamine supplementation, nor alteration in the anti-oxidation capacity of the glutathione system assessed through TBARS ratio calculation. L-glutamine supplementation had no impact on the glycolitic path and insulin secretagogue. It is concluded that the increase in urea and creatinine serum levels and the reduction of the estimated Glomerular Filtration Rate occur probably due to the difficulty of the aged kidneys to metabolize protein-sourced supplements. Although they are not clinically significant, these alterations impose a rigorous control in the evaluation of the kidney function parameters during the L-glutamine supplementation with doses of 0.5g/kg/day on middle-aged and elderly individuals. In absence of additional stress, the L-glutamine supplementation does not alter the organic reactions standard of oxidative stress, pertaining to aging, not justifying, therefore, its usage in these situations.